Development Educational Game Model “Rekreasiku” to Improve Childhood Language Literacy - Barokah Widuroyekti; Hadiqotul Luluk; Iswati Iswati (Indonesia Emerging Literacy Education, 2022)
The purpose of this research is to develop a valid and effective Recreational Educational Game for increasing early childhood language literacy. Literacy is a good culture to develop, literacy is reading, listening, writing, and speaking, the basic things that must be done. Unesco said that Indonesia ranks second from the bottom in terms of world literacy, meaning that people's interest in reading and writing is very low. Among the factors that influence literacy are habituation and the media. The type of research used is research and development from Bord and Gall. The research subjects were 2 Early Childhood Education Programs units in Jember. The instruments used were model validation sheets, educational game questionnaire sheets, and literacy tests. Data were analyzed by descriptive quantitative. So as to create an Educational Recreation Game activity to increase literacy in early childhood without leaving the principle of playing for children. The Educational Games carried out refer to the curriculum that has been used by Early Childhood Education Programs teachers. The results of the study show that the Educational Recreation Game that was developed is valid as an appropriate learning medium for increasing early childhood literacy. Effective for increasing children's language literacy.